INCREASING LEARNING OUTCOMES RHYTMIC GYMNASTICS ACTIVITIES THROUGH ACTIVE LEARNING APPROACHES - Abdullah; Asmawi, Moch.; Samsudin (International Journal of Engineering Technologies and Management Research, 2019)
The application of the rhythmic gymnastics learning approach must be in accordance with the characteristics of students, for that it requires an innovative and active learning approach according to all the existing characters. The method used is action research using Kemmis and Mc. Taggart with the design of planning, observation, action and reflection. The results showed an increase in rhythmic gymnastics learning outcomes. This is evidenced by the average in the pre cycle which is 43.2 with a percentage of 42.29%, in the first cycle increased to 63.9 with a percentage of 55.26% and in the second cycle increased to 87.3 with a percentage of 100%. So, it can be concluded that the active learning approach can improve the learning outcomes of rhythmic gymnastics. Because the application of an active learning approach is adapted to the characteristics of students who want to learn and facilitate the learning process in understanding the rhythmic gymnastics methods.